Respostas

2013-05-11T16:29:09-03:00

E = (2√2 + √3 + √2 - √3) / √3

√3 - √3 = 0
2√2 + √2 = 3√2

E = 3√2 / √3 ⇒ Multiplicando o numerador e o denominador por √3 ⇒
E = (3√2 . √3) / (√3 . √3) ⇒
E = 3√6 / √9 ⇒ Como √9 = 3 ⇒
E = 3√6 / 3 ⇒ Cortando 3 com 3 ⇒
E = √6

Resposta: D)

2013-05-11T16:58:43-03:00

 

 

E = (2√2 + √2+ √3  - √3) 

---------------------------------

               √3

E = (2√2 + √2)      3√2                    3√6

--------------------=   ---------* (√3)= -------=  cancela o 3 obtemos o valor para E=√6

               √3              √3                      3

 

 

Espero ter ajudado

Thiau.